18F-FDG PET/CT and MRI in the Management of Multiple Myeloma: A Comparative Review - Mesguich, Charles; Hulin, Cyrille; Latrabe, Valérie; Lascaux, Axelle; Bordenave, Laurence; Hindié, Elif (Frontiers in Nuclear Medicine, 2022)
During the last two decades, the imaging landscape of Multiple Myeloma (MM) has evolved with whole-body imaging techniques such as FDG-PET/CT and MRI replacing x-ray skeletal survey. Both imaging modalities have high diagnostic performance at initial diagnosis of MM and are key players in the identification of patients needing treatment. Diffusion-weighted MRI has high sensitivity for bone involvement while FDG-PET/CT baseline parameters carry strong prognostic value. The advent of more efficient therapeutics, such as immunomodulatory drugs and proteasome inhibitors, has called for the use of sensitive imaging techniques for monitoring response to treatment. Diffusion-weighted MRI could improve MRI specificity for tumor response evaluation, but questions remain regarding its prognostic value. Performed at key time points of treatment in newly diagnosed MM patients, FDG-PET/CT findings have high prognostic value regarding relapse risk and survival. The deployment of minimal residual disease detection at the cellular or molecular level may raise interrogations on the role of these imaging techniques, which will be addressed. This review summarizes and outlines the specificities and respective roles of MRI and 18-FDG PET/CT in the management of MM.